Evaluasi Rekayasa Perkuatan Jalan Tambang Menggunakan Material Limestone Reject dan Metode Stone Column Pada Kondisi Slippery di Kabupaten Balangan - Pikar Chandra Syah Putro; Rani Nasrasyam Zalma; Dimas Wahyu Pamungkas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
High rainfall intensity and surface water accumulation on mine haul roads frequently cause slippery conditions, leading to a reduction in Effective Working Hours (EWH) of heavy equipment and disruptions in overburden removal activities. This inefficiency results in substantial production losses, estimated at approximately IDR 403 million per hour due to waiting times and operational delays. This study aims to evaluate the effectiveness of haul road reinforcement engineering through the utilization of local limestone reject material as a surface layer and the stone column method as a subgrade reinforcement system under slippery conditions in Balangan Regency, South Kalimantan. The evaluation was conducted on a 21 km section, equivalent to 66% of the total 31.9 km haul road network at PT Saptaindra Sejati (SIS) Job Site SERA, focusing on segments with the highest frequency of slippery occurrences. Additional measures included optimizing road geometry design (double crossfall), constructing grader parking areas, and improving surface compaction techniques. The evaluation results revealed a reduction in slippery duration from an average of 1.32 hours to 0.5 hours per rainfall event, an increase in soil bearing capacity by 167%, a 15% reduction in fuel consumption, and a 20% decrease in hauler tire wear. Overall, the integrated implementation of limestone reject and stone column proved to be an effective, efficient, and sustainable engineering solution for improving subgrade strength, enhancing drainage performance, and increasing operational efficiency of haul roads in high-rainfall mining environments such as Balangan.